2014
DOI: 10.1177/2156759x0001800110
|View full text |Cite
|
Sign up to set email alerts
|

School Counseling Websites: Do They Have Content that Serves Diverse Students?

Abstract: The 12 diversity dimensions of the ASCA Ethical Standards (ASCA, 2010) provided a framework for examining whether a statewide sample of high school counseling websites (N = 312) had content for diverse students and their families. Many websites offered little content related to those dimensions, and content was especially low for some groups including LGBT students and immigrant students. Findings indicate a need for school counseling websites to have nondiscrimination statements, text/documents, links, and fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Content analysis was determined to be the best method to conduct this study as a content analysis systematically quantifies and characterizes observed messaging/content in both print and visual messaging (Berelson, 1952; Neuendorf, 2017). As a research methodology, a content analysis has been considered in another study that incorporated ASCA diversity standards as a framework for examining websites high school counselor websites (Kennedy & Baker, 2014). The alignment of the methodology with the focus of this study as well as the applicability to school counseling standards made content analysis an appropriate methodology for this study.…”
Section: Methodsmentioning
confidence: 99%
“…Content analysis was determined to be the best method to conduct this study as a content analysis systematically quantifies and characterizes observed messaging/content in both print and visual messaging (Berelson, 1952; Neuendorf, 2017). As a research methodology, a content analysis has been considered in another study that incorporated ASCA diversity standards as a framework for examining websites high school counselor websites (Kennedy & Baker, 2014). The alignment of the methodology with the focus of this study as well as the applicability to school counseling standards made content analysis an appropriate methodology for this study.…”
Section: Methodsmentioning
confidence: 99%
“…The transition from high school to college is a formative one. For lesbian, gay, bisexual, transgender, and questioning (LGBTQ) youth, this transition also presents distinct challenges, as LGBTQ students face unique stressors such as coming out and/or transitioning gender, nonaffirming campus climates [1e3], and limited access to inclusive academic, health, and mental health services [2,4,5]. These stressors may be even more pronounced for LGBTQ students of color, who also experience racism and discrimination [6,7].…”
mentioning
confidence: 99%
“…Yet, the barriers endorsed by LGBQQ students suggest that schools need to do better. While campus counseling centers report outreach to LGBTQ students [13], most counseling center Web sites lack LGBTQ-inclusive content [4,5]. This oversight is striking given student preferences for online information seeking [14] and the increase in LGBTQ-affirming resources [15e18].…”
mentioning
confidence: 99%